1999
DOI: 10.1074/jbc.274.19.13690
|View full text |Cite
|
Sign up to set email alerts
|

Rap1B and Rap2B Translocation to the Cytoskeleton by von Willebrand Factor Involves FcγII Receptor-mediated Protein Tyrosine Phosphorylation

Abstract: Stimulation of human platelets with von Willebrand factor (vWF) induced the translocation of the small GTPases Rap1B and Rap2B to the cytoskeleton. This effect was specifically prevented by an anti-glycoprotein Ib monoclonal antibody or by the omission of stirring, but was not affected by the peptide RGDS, which antagonizes binding of adhesive proteins to platelet integrins. Association of Rap2B with the cytoskeleton was very rapid, while translocation of Rap1B occurred in a later phase of platelet activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 30 publications
2
77
1
3
Order By: Relevance
“…Binding of VWF to GPIb-V-IX upregulates integrin αIIbβ3 affinity (Asazuma et al, 1997;Kasirer-Friede et al, 2004;Milner et al, 1998;Munday et al, 2000;Nesbitt et al, 2002;Torti et al, 1999;Yuan et al, 1999). The integrin can then bind to VWF, thereby enhancing adhesion, and contributing to thrombus formation by binding to fibrinogen.…”
Section: The Gpib-v-ix Complexmentioning
confidence: 99%
See 3 more Smart Citations
“…Binding of VWF to GPIb-V-IX upregulates integrin αIIbβ3 affinity (Asazuma et al, 1997;Kasirer-Friede et al, 2004;Milner et al, 1998;Munday et al, 2000;Nesbitt et al, 2002;Torti et al, 1999;Yuan et al, 1999). The integrin can then bind to VWF, thereby enhancing adhesion, and contributing to thrombus formation by binding to fibrinogen.…”
Section: The Gpib-v-ix Complexmentioning
confidence: 99%
“…The binding of VWF to GPIb under shear stress can stimulate calcium mobilization (Kroll et al, 1991;Mazzucato et al, 2002;Milner et al, 1998;Nesbitt et al, 2002;Yap et al, 2000), protein kinase C (PKC), protein kinase G (PKG) (Li et al, 2003;Yap et al, 2000), phosphoinositide 3-kinase (PI3K) (Jackson et al, 1994;Munday et al, 2000;Yap et al, 2000) and cytoskeletal rearrangements (Torti et al, 1999;Yuan et al, 1999). VWF binding also upregulates integrin αIIbβ3 affinity indirectly through the stimulation of ADP secretion (Moake et al, 1988).…”
Section: Signalling Through Gpibmentioning
confidence: 99%
See 2 more Smart Citations
“…In platelets, the GPIb-IX-V complex, a member of the leucine-rich GP gene family, is the main receptor for vWF (58). In 1999, Torti et al (59) revealed that the translocation of Rap1B and Rap2B to the cytoskeleton was induced by vWF, following binding of vWF to the GPIb-IX-V complex through a GP IIb/IIIa-independent mechanism. In a previous study, Rap2B was prevented from associating with the cytoskeleton by cytochalasin D, which did not inhibit platelet aggregation (60).…”
Section: Translocation Of Rap1b and Rap2b To The Cytoskeleton Via Vonmentioning
confidence: 99%